Physical characterization of bamboo schizostachyum grande fiber treated by silane coupling agent for hydrophobic applications - Roseli, Adyla Illyana; Mat Hassana, Nik Normunira; Yahya, Nur Faezah; Atil, Aida Atiqah; Darlis, Nofrizalidris; Roslan, Mohd Nazrul; Tuan Ismail, Tuan Noor Hasanah (2024)
The use of bamboo fiber has gained significant attention in various industries, such as construction, packaging, and automotive applications. This study focused on the Schizostachyum Grande species of bamboo fiber and investigated the effect of treatment with a silane coupling agent on its physical characteristics. The characterization was done using techniques such as Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA), and Fourier-Transform Infrared Spectroscopy (FTIR) analysis. Results showed that treated bamboo fiber exhibited a stronger and more closely bound fiber structure with a surface that reacted better to silane coupling agents, as seen in SEM images. TGA analysis revealed that thermal degradation occurred completely at a higher temperature for treated bamboo fiber compared to untreated bamboo fiber. FTIR analysis also showed changes in functional groups, with the appearance of peaks related to Si-O-Si and Si-O-C stretching vibrations after treatment. Overall, this study highlights the effectiveness of silane coupling agent treatment in enhancing the surface morphology and chemical properties of bamboo fiber, making it suitable for hydrophobic applications